The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.iecr.9b05132
|View full text |Cite
|
Sign up to set email alerts
|

Intensified Catalytic Transfer Hydrogenation of Sunflower Oil Using Ultrasound

Abstract: The present work deals with the catalytic transfer hydrogenation (CTH) of sunflower oil focusing on establishing the best conditions of ultrasonic operating and reaction parameters to maximize the extent of hydrogenation of sunflower oil. The processing is based on the use of 5% Pd/C as the catalyst, ammonium formate as the hydrogen donor, and water as solvent. The effect of ultrasonic power, ultrasonic frequency, temperature, speed of agitation, catalyst loading, and water quantity on the extent of CTH has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Sound waves with a frequency higher than 20 kHz are called ultrasonic waves. When ultrasonic waves propagate in the medium, they will produce a series of effects such as mechanical effects, thermal effects, and cavitation 18 . They have a good emulsification effect and can promote a reaction 19 , so ultrasonic assistance can greatly increase a reaction rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sound waves with a frequency higher than 20 kHz are called ultrasonic waves. When ultrasonic waves propagate in the medium, they will produce a series of effects such as mechanical effects, thermal effects, and cavitation 18 . They have a good emulsification effect and can promote a reaction 19 , so ultrasonic assistance can greatly increase a reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…The use of ultrasonic technology instead of the activation of conventional hydroprocessing catalysts also ensures the safety of the conjugate conversion process 20 . Studies have shown that ultrasound can cause rapid pres-sure changes 21 , and a synergistic effect between the catalyst and ultrasound 18 , paving the way for reactions that are usually not feasible under quiet conditions. This synergy between ultrasound and catalysis is mainly observed in the presence of solid catalysts.…”
Section: Introductionmentioning
confidence: 99%